2016
DOI: 10.1039/c6ta01441k
|View full text |Cite
|
Sign up to set email alerts
|

A self-healable and easily recyclable supramolecular hydrogel electrolyte for flexible supercapacitors

Abstract: A novel ferric ion cross-linked PAA supramolecular hydrogel electrolyte (Fe3+/PAA) with self-healing ability and easy-recyclability is fabricated and assembled with graphene foam supported polypyrrole electrodes (GF@PPy) to test its electrochemical performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
179
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(192 citation statements)
references
References 54 publications
5
179
0
Order By: Relevance
“…Chemical structure of various polymers for the self-healing energy harvesting and storage devices. a) PVA: poly(vinyl alcohol) [99,127,128] , b) PAA: polyacrylic acid [71,80,97,98] , c) PDMS: polydimethylsiloxane [42,77,83] , d) PDMAA: poly(N,N-dimethylacrylamide) [51,52] , e) PMCMA-co-PCMA: poly[2-(ethylcarbamoyloxy)ethyl methacrylate-co-2-(ethylcarbamoyloxy)ethyl acrylate [56] ], f) PCL: polycaprolactone [69,75] , g) bPEI: branched polyethylenimine [62,71,80] , h) PU: polyurethane. [43,81,[91][92][93] www.advancedsciencenews.com Adv.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical structure of various polymers for the self-healing energy harvesting and storage devices. a) PVA: poly(vinyl alcohol) [99,127,128] , b) PAA: polyacrylic acid [71,80,97,98] , c) PDMS: polydimethylsiloxane [42,77,83] , d) PDMAA: poly(N,N-dimethylacrylamide) [51,52] , e) PMCMA-co-PCMA: poly[2-(ethylcarbamoyloxy)ethyl methacrylate-co-2-(ethylcarbamoyloxy)ethyl acrylate [56] ], f) PCL: polycaprolactone [69,75] , g) bPEI: branched polyethylenimine [62,71,80] , h) PU: polyurethane. [43,81,[91][92][93] www.advancedsciencenews.com Adv.…”
Section: Discussionmentioning
confidence: 99%
“…b) Self-healing of a dumbbell-shaped hydrogel at room temperature: i) the hydrogel after being cut, ii) the hydrogel after healing for 24 h. Reproduced with permission. [98] Copyright 2016, The Royal Society of Chemistry. c) Schematic illustration of the synthesis of self-healable PVA-g-PAA/KCl hydrogel electrolytes.…”
Section: Self-healing Electrolytes For Supercapacitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, novel polymeric electrolytes which are intrinsically self-healable have been studied further. [100][101][102] Recently, Huang et al has reported a new self-healing electrolyte composed of polyacrylic acid and hybrid vinyl-silica nanoparticles (VSNPs-PAA) (Figure 5b). [103] The PAA polymer chains provided abundant reversible intermolecular hydrogen bonding, while the VSNPs reinforced the mechanical properties and covalently crosslinked the PAA polymer chains.…”
Section: Self-healing Abilities In Response To External Mechanical Damentioning
confidence: 99%
“…[100][101][102] Among these studies, efforts were mainly made concerning the recovery of electrode conductivities and integrity of the overall the configuration. Furthermore, the conventional PVA-based electrolytes with relatively low self-repair capability were frequently employed, which likely limited the overall self-healing performance of the corresponding supercapacitors.…”
Section: Self-healing Abilities In Response To External Mechanical Damentioning
confidence: 99%